Vascular sclerosing effects of bleomycin on cutaneous veins: a pharmacopathologic study on experimental animals - AlGhamdi, Khalid Mohammed; Kumar, Ashok; Ashour, Abdelkader Elbadawy Abbas; Al- Rikabi, Ammar Cherkess; AlOmrani, Abdullah Hasan; Ahamed, Shaik Shaffi (Sociedade Brasileira de Dermatologia, 2017)
BACKGROUND:: Varicose veins and the complications of venous disease are common disorders in humans.